THE EFFECT OF PSYCHOLOGICAL WELL-BEING ON THE STUDENT’S INTEGRAL INDIVIDUALITY STRUCTURE - D. G. Orlova (Obrazovanie i Nauka, 2017)
Introduction. New Federal State Standards of the higher education impose increased requirements not only to the level of professional competence of university graduates, but also to their personal readiness for implementation of successful professional activity. Psychological well-being is one of the integrative personal bases defining effective and full realization of labour functions by an expert. This has caused the research relevance stated in the article.The aim of this article is to analyze the specifics of the relationships of students’ integrated individuality of depending with the expression level of psychological well-being.Methodology and research methods. Methodological base of work involve the concept of psychological well-being by K. Riff, and the theory of integrated identity by V. S. Merlin. The research was conducted with the use of a package of diagnostic methods: «Scales of psychological well-being» by K. Ryff modified by D. G. Orlova; methods of studying the temperament by J. Strelau (adaptation by N. N. Danilova and A. G. Shmelyov); Structure Of Temperament Questionnaire by V. M. Rusalov (STQ); Five-Factor Personal Questionnaire (5PFQ) in A. B. Khromov’s adaptation.Results and scientific novelty. The retrospective analysis of researches on a psychological well-being phenomenon in foreign and Russian psychology is carried out. The author made an attempt to show the principle of polymorphism as one of the fundamental principles of the integrated identity theory on the example of studying the role of psychological well-being in the structure of a student identity. An empirical part of the present research, carried out on the basis of four higher educational institutions of Perm, showed the existence of general characteristics and significant distinctions on indicators of neurodynamic, psychodynamic and personal levels of integrated identity between two groups of respondents – students with low and high values of psychological well-being. In each group it was succeeded to reveal some unique correlations in interrelations of indicators of these levels. Interrelations of temperament indicators between nervous system and personality indicators, as well as interrelation of personality indicators between each other are specific to a group with low psychological well-being. Only interrelations of temperament indicators between each other are specific to a group with high psychological well-being.Practical significance. The materials and findings provided in the article can be used for organization of the educational process in higher educational institutions.